IMPLEMENTATION MECHANISM OF CAREER GUIDANCE AT THE UNIVERSITY - Konstantin A. Rerekin; Anna P. Simonenkova; Julia G. Buzueva (Высшее образование в России)
The labor market is constantly changing. These changes apply to the needs of industries in professional staffing structure and training levels of professionals involved in the economic processes. The most important task of Russian higher education is to meet the needs of the economy for highly qualified personnel by improving the competitiveness and mobility of graduates in the labor market.